2020
DOI: 10.2196/16300
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Performance of Complementary Clinical Information Technologies: Analysis of a Survey of General Practitioners

Abstract: Background The benefits from the combination of 4 clinical information systems (CISs)—electronic health records (EHRs), health information exchange (HIE), personal health records (PHRs), and telehealth—in primary care depend on the configuration of their functional capabilities available to clinicians. However, our empirical knowledge of these configurations and their associated performance implications is very limited because they have mostly been studied in isolation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…According to our findings, the strength of barriers and the importance of strategies differed between GPs based on gender, with female participants perceiving barriers as higher and strategies as more important than their male colleagues. This is in line with studies reporting that being male was associated with using digital health technology 27 , 50 while being female was associated with lower digital health adoption 49 . Other studies found no gender-based differences for digital health adoption 24 or even a higher usage for female participants 51 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to our findings, the strength of barriers and the importance of strategies differed between GPs based on gender, with female participants perceiving barriers as higher and strategies as more important than their male colleagues. This is in line with studies reporting that being male was associated with using digital health technology 27 , 50 while being female was associated with lower digital health adoption 49 . Other studies found no gender-based differences for digital health adoption 24 or even a higher usage for female participants 51 .…”
Section: Discussionsupporting
confidence: 91%
“…While extensive research has studied influencing factors to digital health adoption 17 , 21 , 24 , 49 , no study has investigated factors influencing adoption barriers or improvement strategies. According to our findings, the strength of barriers and the importance of strategies differed between GPs based on gender, with female participants perceiving barriers as higher and strategies as more important than their male colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps if they had sought to identify five clusters, they would have identified more-defined early and late majority groups as well. Beyond Kwon and Johnson (2013), the use of cluster analysis for diffusion research is further evidenced in studies like Schedler et al (2019) and Poba-Nzaou et al (2020). Guillamet et al (2018) utilize clustering methods to analyze electronic health records, identifying clusters of chronic obstructive pulmonary disease (COPD) patients.…”
Section: Methodsmentioning
confidence: 99%